PTU-126 Mortality Associated With Hepatic Encephalopathy In Patients With Severe Liver Disease. (9th June 2014) - Morgan, CL; Jenkins-Jones, S; Radwan, A; Conway, P; Currie, CJ
Abstract : Introduction: Despite hepatic encephalopathy (HE) being a common complication of severe liver disease, there are comparatively few data describing the epidemiology of the condition. The aim was to characterise mortality risk for patients with HE. Methods: The study was conducted using data from the Clinical Practice Research Datalink (CPRD). Patients with a record of first diagnosis of liver disease were identified between 1998 and 2012. Two Cox Proportional Hazard models were generated. The first followed the whole liver disease cohort with HE modelled as a binary time-dependent variable in quarterly segments. The second compared patients identified with HE to non-HE controls matched at a ratio of 1:1 on age, gender, year of first diagnosis of liver disease, liver disease duration and Baveno IV status. Results: 17, 030 patients were identified with a diagnosis of liver disease, of whom 551 (3.2%) had a HE diagnosis. Of patients identified with HE, 304 of 551 (55.2%) died during the follow-up period, compared with 6, 693 of 16, 479 (40.6%) of those without HE (p < 0.001). In the Cox Proportional Hazard model, the hazard ratio of HE modelled as a time-dependent variable was 1.43 (95% CI 1.20–1.70; p < 0.001) (Table 1 ). 389 of the 551 HE patients (70.6%) could be matched to non-HE controls. 226 HE patients (58.1%) died during the follow up period compared with 126 (32.4%) controls. The hazard ratio for time to death was 2.28 (95% CI 1.82–2.87; p < 0.001). Conclusion: HE substantially increased mortality risk in patients with chronic liver disease. Disclosure of Interest: C. Morgan Consultant for: Norgine; S. Jenkins-Jones Consultant for: Norgine; A. Radwan Employee of: Norgine; P. Conway Employee of: Norgine; C. Currie Consultant for: Norgine.